Pengaruh Model Pembelajaran Kooperatif Tipe Team Games Tournament (TGT) berbantuan Media Kotak Kartu Misterius (KOKAMI) terhadap Aktivitas dan Hasil Belajar Siswa pada Mata Pelajaran IPA Biologi di SMP Negeri 19 Palu - Aziza, Nurul Inaya; Jamhari, Mohammad; Windarsih, Yulia; Shamdas, Gamar; Rafiqa, Rafiqa; Jayanti, Zulaikhah Dwi (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to determine the effect of Team Games Tournament (TGT) cooperative learning model assisted by Mysterious Card Box (KOKAMI) media on students' Biology Science learning activities and outcomes at SMP Negeri 19 Palu. Teacher-centered learning models tend to reduce student interaction and participation, so a more active and innovative approach is needed, such as TGT with KOKAMI media to improve student learning activities and outcomes. The research method used was quasi-experiment with post-test only control group design. Data were collected through activity observations and learning outcome tests, with samples taken purposively. Data analysis was carried out quantitatively through comparison of the average scores of experimental and control classes. The t-test results using SPSS ver.29 showed a significance value (2-tailed) of 0.001 < Î± 0.05. Thus, the alternative hypothesis (H1) which states that there is a significant difference in activity and learning outcomes between the experimental and control classes is accepted. This shows that the application of the TGT cooperative model assisted by KOKAMI media has a real effect in increasing the activity and learning outcomes of Biological Science. This model has the potential to be applied more widely to improve the quality of science learning at the secondary school level.